STUDI LITERATUR: PERAN PANCASILA UNTUK MEMBANGUN KARAKTER BANGSA - Muhamad Tarom (LPPM UNSAP, 2026)
This study examines the role of Pancasila in shaping the character of the Indonesian nation through a qualitative approach. The rapid development of globalization has influenced lifestyle changes, especially among younger generations, which has led to a decline in the internalization of Pancasila values. This research aims to analyze the values contained in each principle of Pancasila and their relevance in character building. Data were collected through literature study, observation, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that each principle of Pancasila contributes significantly to character formation. The first principle strengthens religious character and tolerance, the second promotes humanity and empathy, the third reinforces unity and nationalism, the fourth develops democratic attitudes, and the fifth emphasizes social justice. These values are essential in addressing moral crises, social conflicts, and inequality in society. The study concludes that Pancasila is not only the foundation of the state but also a moral guideline that can shape individuals into responsible, ethical, and socially aware citizens. Strengthening the implementation of Pancasila values through education and social environments is necessary to build a strong national character in the era of globalization..